Perceived Organizational Support and Work Engagement in Malaysian Banking Industry - Mahmood, Nor Asiah; Saad, Abidah; Ishak, Suhaida (Journal of Ecohumanism, 2024)
This study focuses on the predictive effect of Perceived Organizational Support (POS) to Work Engagement (WE) in the Malaysian Banking Industry, Peninsular Malaysia. The population in this study were all employees employed in Malaysian banking industry. The method used in this research is quantitative descriptive studies using a simple descriptive approach and Structural Equation Modelling- Partial Least Squared (SMART PLS-3) analysis to test the study hypotheses. This study found that the hypotheses is supported which show the direct relationship between the perceived organizational support and work engagement. Perceived organizational support is the belief of employees that if managers are concerned about their employees' commitment to the organisation, employees will be concerned about the organization's commitment to them. The implication of this study is that employers should ensure the employees knows that they are getting support in workplace from organization as this will affect their work engagement at workplace as this may affect their performance.